Cadeia produtiva, manejo e conservação da fava d’anta (Dimorphandra gardneriana tulasne) da floresta nacional do Araripe-Apodi, região semiárida do nordeste do Brasil - Alcântara, Micaelle Sônia de (2018)
Forests play extremely relevant roles, both ecologically, economically and even socially. One of the policies for sustainable development and conservation of nature is the creation of spaces for environmental protection, being in Brazil, such areas called Conservation Units (UC). Some UC categories allow for anthropogenic intervention, including for the extractive use of sustainable resources. The objective of the present research was to characterize the productive chain and management techniques of the fava d'anta, Dimorphandra gardneriana, in two overlapping UCs, the Araripe Environmental Preservation Area (APA) and the Araripe-Apodi National Forest, in the semiarid state of Ceará. In addition, the impacts that extractivism can have on fava d'anta populations and their phytochemical characterization were defined. The work was carried out with the main extractive communities located in the buffer zone, in the municipality of Jardim-CE. In order to define the sociodemographic and socioeconomic profile of the collectors and definition of the productive chain, extractive impacts and the characteristics of fava d'anta management, two collection strategies were carried out: participant observation and semi - structured interviews. Interviews were conducted with collectors, intermediaries and ICMBio employees. To identify the geographic dimension and the availability of the natural resource, the participatory mapping was used with the help of the geographic information system (GIS) technology. In order to investigate possible impacts on the fava d'anta population, phenology, fruit morphometry and phytochemical profile were investigated in areas with different human, wild, managed and cultivated areas. The exploitation of the resource by the communities has great economic importance for the region, while its productive chain has obstacles regarding the valorization of the collectors, market efficiency, structure and processing of the resource, needing public attention and greater organization. The collection of the resource occurs in a variety of management systems, which enables the sustainability of the activity to improve the returns of the collectors; however, the collection process poses risks to the health and safety of the collectors and possible impacts to fava d'anta populations in areas. Higher productivity, fruit viability and phenolic compounds production occur in growing areas or in the tolerance system, allowing higher economic returns to the collectors.